The Effect of Problem Solving Learning Method towards Indonesian Subject Learners’ Learning Outcomes - Mela Sundari; Suhirman Suhirman; Heny Friantary (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
This study was aimed to reveal the effect of problem solving method on the students’ Indonesian subject learning outcomes in the second grade students of IPA Class of SMA Negeri 5 Lebong. This study was designed by using a quantitative approach implementing a quasi experimental method. This method allowed the researchers to study a control class and an experimental class, but the control class did not have a crucial function to control the external variables which influenced the implementation of the experiment. Based on the result of this research, it could be concluded that there was the effect of problem solving on the Indonesian learners’ learning outcomes at the second grade students of IPA Class of SMA Negeri 5 Lebong. It triumphantly revealed that there was the influential effect of the implementation of the problem solving learning method. It could be seen that thitung = 7,947 > ttabel =2,048 with the significance level 0,05%. The alternative hypothesis proved that the effect of problem solving on the Indonesian learners’ learning outcomes at the second grade students of IPA Class of SMA Negeri 5 Lebong was acceptable.